Reconstruction of unintended interactions in synthetic gene circuits from time-series perturbation experiments. Issue 23 (2022) - Wang, Yu; Jacobsen, Elling W.
Abstract: Synthetic gene circuit behaviour can be qualitatively different from the intended one due to effects from unintended interactions with the host cell. Such unintended interactions are essentially inevitable, since the circuits rely on the cellular resources in the host cell. The paper considers the feasibility of reconstructing such unintended interactions from time-series perturbation experiments. Identifying the specific interactions with the host cell is a prerequisite to mitigate their effects on the circuit behaviour. Previously proposed methods either cannot distinguish such unintended interactions from the intended direct interactions between circuit genes or require perturbing all the circuit genes by unique perturbations in separate experiments, which typically imply very costly experiments. We show herein that it in principle is feasible to identify all unintended interactions with the host cell from one single perturbation experiment. We also discuss fundamental limitations of steady-state data. The results are illustrated using a recently implemented three-gene cascade synthetic circuit in E. coli.